Estimating human trafficking worlwide: a multi-mode strategy - Van Dijk, Jan (Researching hidden populations, 2015)
In this article, the author presents the results of an in-depth analysis of the production of statistics by Eurostat on formally identified victims of trafficking in human beings in Europe. He concludes that the concept of an identified victim of trafficking in human beings has different meanings in different European Union member States and that the identification process is organized differently as well. On the basis of those regional results, he argues that statistics on the number of recorded victims of human trafficking cannot be used as a reliable measurement of the extent of trafficking in human beings in a country, neither in the European Union nor elsewhere. As follow-up to this critical assessment, the author argues in favour of a worldwide programme for the collection of survey-based estimates of human trafficking and, to that end, presents a methodological strategy combining various modes of data collection.